Neutrophils inhibit γδ T cell functions in the imiquimod-induced mouse model of psoriasis - Costa, Sara; Bevilacqua, Dalila; Caveggion, Elena; Gasperini, Sara; Zenaro, Elena; Pettinella, Francesca; Donini, Marta; Dusi, Stefano; Constantin, Gabriela; Lonardi, Silvia; Vermi, William; De Sanctis, Francesco; et al. (Frontiers in Immunology, 2022)
Psoriasis is a chronic skin disease associated with deregulated interplays between immune cells and keratinocytes. Neutrophil accumulation in the skin is a histological feature that characterizes psoriasis. However, the role of neutrophils in psoriasis onset and development remains poorly understood. In this study, we utilized the imiquimod (IMQ)-induced mouse model of psoriasis to elucidate the specific contribution of neutrophils to psoriasis development. By analyzing disease development/progression in neutrophil-depleted mice, we now report that neutrophils act as negative modulators of disease propagation and exacerbation by inhibiting gammadelta T cell effector functions via nicotinamide adenine dinucleotide phosphate (NADPH) oxidase-mediated reactive oxygen species (ROS) production. We also report that Syk functions as a crucial molecule in determining the outcome of neutrophil and gammadelta T cell interactions. Accordingly, we uncover that a selective impairment of Syk-dependent signaling in neutrophils is sufficient to reproduce the enhancement of skin inflammation and gammadelta T cell infiltration observed in neutrophil-depleted mice. Overall, our findings add new insights into the specific contribution of neutrophils to disease progression in the IMQ-induced mouse model of psoriasis, namely as negative regulatory cells.